Sistema de filtrado para el tratamiento del recurso hídrico que ingresa al humedal el burro (2021)
Pollution, disease and danger of extinction; are the main consequences that threaten urban wetlands in Bogotá, due to the misuse that is given to the bodies of water that cross the city, based on this, this project seeks to provide an alternative to this need through the principles of sedimentation laminar and phytoremediation.